CHARACTER AND MORAL VALUE IN “THE SOUND OF MUSIC” BY ROBERT WISE - AAN HANDAYANI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2022)
This research aims to analyze the characters and moral values ??contained in the film "The Sound of Music" by Robert Wise. Based on the theories of character and moral values ??collected, four main points are analyzed, they are: 1) The character appear in "The Sound of Music" by Robert Wise based on the theory put forward by Russel (2009), there are some figures who must be analyzed based on their character, 2 ) The moral values that ??appear in "The Sound of Music" by Robert Wise based on the theory put forward by Borba (2001). 3) There are 3 kinds of characters that appear in the characters in "The Sound of Music" by Robert Wise based on Russel’s theory, those are  the Protagonist, the main protagonist played by Maria and the Von Trapp Family and the sisters in the monastery, the Antagonist, played by The Baroness and Herr Zeller , and Foil  character played by Rolfe and Franz, 4) There are 7 types of moral values ??that appear in "The Sound of Music" by Robert Wise based on Borba’s theory , they are: respect, kindness, conscience, self-control, justice, empathy and tolerance, respect is the most dominant moral values ??of all moral values ??that arise. ABSTRAKPenelitian ini bertujuan untuk menganalisis karakter tokoh-tokoh dan nilai moral yang terdapat pada film “The Sound of Music” oleh Robert Wise. Berdasarkan teori- teori karakter dan nilai moral yang dikumpulkan, maka diperoleh empat point pokok yang dianalisa yaitu: 1) Karakter tokoh-tokoh yang muncul dalam “The Sound of Music” oleh Robert Wise, 2) Nilai moral yang muncul dalam “The Sound of Music” oleh Robert Wise berdasarkan teori yang dikemukakan oleh Borba (2001). 3) Ada 3 macam karakter yang muncul pada tokoh-tokoh dalam “The Sound of Music” oleh Robert Wise berdasarkan teori Russel (2009), yaitu Protagonist, protagonist utama diperankan oleh Maria dan Keluarga Von Trapp beserta para suster di biara, Antagonist, yang diperankan oleh The Baroness dan Herr Zeller, dan Foil diperankan oleh Rolfe dan Franz, 4) Ada 7 macam jenis nilai moral yang muncul dalam “The Sound of Music” oleh Robert Wise yaitu : rasa hormat, kebaikan, kesadaran diri, pengendalian diri, keadilan, empati dan toleransi, rasa hormat merupakan nilai moral yang paling mendominasi dari keseluruhan nilai-nilai moral yang muncul.